Analysis of mangrove forest vegetation in Wambona Village, South Wakorumba District, Muna Regency, Indonesia - La Ode Hamruddin Momo; Wa Ode Sri Rahayu (Sekolah Tinggi Ilmu Pertanian Wuna, 2018)
The study aims to determine the type of vegetation that composes mangrove forests and their zoning patterns, to know the composition of mangrove vegetation types and to determine the level of mangrove forest diversity. This study was determined based on the characteristics of the research location ranging from those close to residential areas to those located close to the beach. The method used is systematic sampling which consists of nine observation blocks and each block is divided into four circular research plots. There are 9 types of vegetation that compose mangrove forests in Wambona Village, Wakorsel District, i.e. Avicenna alba BI, Bruguiera hainnessi, Bruguiera gymnorrhiza (L.) Lamk, Ceriops tagal (Perr), Rhizophora mucronata Lamk, Rhizophora stylosa Griff, Sonneratia alba J.E. Smith, Caseolaris sonneratia (L.) Engl. and Bruguiera parviflora (Roxb.) Important Value Index (IVI) of mangrove vegetation in Wambona Village, Wakorsel District namely; 300% for tree level, pole, stake and 200% for seedling level. Diversity of mangrove vegetation types in Wambona Village, Wakorsel District as a whole is in the moderate category (moderate stability) with each tree 1.54, pole 1.57, stake 1.49 and seedling 1.64.